Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, spring 1988 - Proescholdt, Market al (1988)
List of birds and locations contributed by Mark Proescholdt with observers Beth Proescholdt, Stephen J. Dinsmore, Robert K. Myers and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed